The Effect Of Audit Findings And Recommendation Follow Ups Of BPK-Ri’s Evaluation On Local Government’s Performance In Districts/Cities East Java Province - Garsuarani Octavianti Ningsih; Sugiharti Binastuti (International Journal of Science, Technology & Management, 2021)
Audit findings and recommendation follow ups are the result of evaluation conducted by BPK. This research aims to investigate the indirect effect of audit findings and recommendation follow ups from the evaluation done by BPK-RI towards the performance of local governments in East Java Province through financial accountability which will be measured by audit opinions from 2013 to 2018. The data used is taken from The Audit Board of The Republic of Indonesia both directly and through website. The data is being tested using STATA. The test result of financial accountability model shows that audit findings on weakness of internal control system, standard deviation, follow up quantity, and recommendation value from the evaluation is indeed influential towards financial accountability. However, for audit findings on non-compliance to regulations in fact does not affect the financial accountability. Furthermore, predicted opinion value is used to test indirect effect which is being connected to performance. The result shows that audit findings and recommendation follow ups from the evaluation do affect indirectly towards the performance of local governments in East Java Province.